Sistem Informasi Penyewaan Arena Futsal dan Alarm Permainan dengan Menggunakan Laravel Berbasis Web di Kota Kraksaan Kabupaten Probolinggo - Andika, Muhammad Hasan; Syafiih, M.; Sya’roni, Wahab (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2024)
The advancement of information technology has transformed the management of futsal businesses, simplifying processes such as court reservations, schedule management, payments, and providing automated notifications to users through a game alarm feature. This system also includes an automatic reporting feature that generates accurate and real-time rental summaries. This study aims to design and implement a web-based futsal rental information system using the Laravel framework, featuring a game alarm to enhance management efficiency. The system is designed to address limitations in futsal rental management and time scheduling, as well as simplify the reporting process, which is currently done manually. The system development follows the waterfall model, which includes requirements analysis, system design, implementation, testing, and maintenance stages. The results show that the implementation of this web-based system significantly improves the efficiency of futsal court management in Kraksaan City, particularly in managing game time, rental reporting, and real-time financial management. The game alarm feature effectively reduces time conflicts between users, while the automatic reporting feature helps business owners track revenue and rental trends easily. The implementation of this system is expected to improve service quality and provide a better user experience, while assisting business owners in managing their operations more efficiently.